Development of system of financial control in the Russian Federation (Путеводитель предпринимателя, 2020)
In article the basic directions and mechanisms offinancial control ofactivity of the domestic enterprises and the organizations which are carrying out manufacture of the goods, work and rendering of services with a view of maintenance of diverse and multilevel requirements of a society, the state and citizens reveal. Increase of efficiency offinancial control, in fair opinion of the author, should be cost not only on the basis of strengthening offiscal functions of the numerous state structures which are carrying out control of execution ofbudgetary powers, but also, first ofall, on all-round state support state and the private enterprises creating a material basis of development of a society, the state and citizens, including, and in theform of the stimulatingfinancial control, capable to render by it the timely help.